Reducing Feature and Temporal Complexity in High-Frequency NILM for Urban IoT Energy Monitoring - Rodrigues, Gabriel Arquelau Pimenta; Serrano, André Luiz Marques; Rocha Filho, Geraldo Pereira; Meneguette, Rodolfo Ipolito; Gonçalves, Vinícius Pereira (Anais do Workshop de Computação Urbana (CoUrb), 2026)
High-frequency non-intrusive load monitoring (NILM) has achieved improved estimation accuracy with the use of harmonic electrical features in smart homes. However, the increased feature space produces significant computational, storage, and communication overheads, especially for scalable urban sensing deployments. Hence, this work investigates the reduction of feature dimensionality and of temporal complexity in high-frequency NILM for urban IoT energy monitoring while preserving predictive performance. A feature importance analysis is conducted using a Random Forest model, resulting in a reduced subset of 19 features, comprising those that together represent 90% of the aggregated importance for all appliances. The results show that models trained with the selected features achieve performance comparable to models trained with the complete feature set, despite a 48.65% dimensionality reduction, which reduces training and inference times and supports scalable deployment in urban sensing infrastructures. Assuming 32-bit floating-point representation, this reduction decreases the input feature vector from 148 bytes to 76 bytes per sample, reducing computational demands. Additionally, a temporal relevance analysis based on mutual information indicates that instantaneous measurements provide the most predictive information. Thus, these findings suggest that accurate high-frequency NILM can be achieved using a reduced feature set and minimal temporal context, promoting efficient deployment on IoT platforms to support scalable urban energy monitoring and more sustainable energy use.